A novel electroactive PPy/HKUST-1 composite film-coated electrode for the selective recovery of lithium ions with low concentrations in aqueous solutions. (20th May 2019) - Wang, Peifen; Du, Xiao; Chen, Tian; Hao, Xiaogang; Abudula, Abuliti; Tang, Keyong; Guan, Guoqing
Abstract: A novel electroactive polypyrrole (PPy)-threaded HKUST-1 metal-organic framework (MOF) composite film was constructed on an electrode. This was achieved by the in situ conversion of CuO in a PPy/CuO composite film to HKUST-1 MOF by a unipolar pulse electro-erosion (UPEE) and in situ coordination method for the recovery of lithium ions (Li + ) with low concentrations in aqueous solutions. The obtained films were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction (XRD), and thermogravimetric analysis. A PPy/HKUST-1 composite film with HKUST-1 anchored in the PPy nanorod networks was successfully formed on the electrode. Extraction of various metal ions, Li +, K +, Na +, Mg 2+, and Cu 2+ with this film was investigated using the electrochemically switched ion exchange technique. The PPy/HKUST-1 composite film exhibited a high selective extraction ability for Li + present in low concentrations. The Li + adsorption capacity reached 37.55 mg/g with an adsorption equilibrium time of less than 25 min owing to the sieving function of the voids and excellent affinity of this film for the Li + ions. It is expected that such an electroactive film can be applied to the separation and recovery of dilute Li resources from various aqueous solutions. Graphical abstract: Image 1 Highlights: An electroactive PPy threaded HKUST-1 composite film was successfully fabricated. Electrochemical adsorption capacity of Li + on the composite film reached 37.55 mg g −1 . The equilibrium time was less than 25 min during electrochemical adsorption process. The film exhibited highly selective extraction ability for Li + ions with a low concentration.